Blob structure and motion in the edge and SOL of NSTX. (28th January 2016) - Zweben, S J; Myra, J R; Davis, W M; D'Ippolito, D A; Gray, T K; Kaye, S M; LeBlanc, B P; Maqueda, R J; Russell, D A; Stotler, D P
Abstract: The structure and motion of discrete plasma blobs (a.k.a. filaments) in the edge and scrape-off layer of NSTX is studied for representative Ohmic and H-mode discharges. Individual blobs were tracked in the 2D radial versus poloidal plane using data from the gas puff imaging diagnostic taken at 400 000 frames s −1 . A database of blob amplitude, size, ellipticity, tilt, and velocity was obtained for 45 000 individual blobs. Empirical relationships between various properties are described, e.g. blob speed versus amplitude and blob tilt versus ellipticity. The blob velocities are also compared with analytic models.